Simulation of hot stamping considering self-tempering - Mori Keitaro; Kubo Masahiro; Okamura Kazuo (MATEC Web of Conferences)
The application of ultra-high-strength steel plates to automobile bodies has progressed to achieve weight reduction and collision safety, with expanding applications of hot stamping (HS) technology for components with tensile strengths of 1.5 GPa or more. HS simulations considering phase transformation for predicting formability, hardenability, and shape accuracy have been reported. The hardness of HS components obtained via die quenching is lower than that of martensitic structures obtained via water quenching, due to self-tempering from the temperature history below the martensite-transformation temperature (Ms point). Few HS simulations consider self-tempering. We established a material model to reproduce self-tempering behaviour accurately and verified hardness prediction after HS. Results: 1) The hardness of water-quenched martensite after tempering was measured, and the activation energy of the tempering reaction was calculated. Then, it became possible to linearly approximate the self-tempering martensite hardness during continuous cooling using the cumulative tempering parameter.2) We developed simulation technology of hot stamping that incorporates the effects of phase transformation, transformation plasticity, and self-tempering. By calculating the tempering parameters at each time step below the Ms point, the accuracy of hardness prediction after HS was confirmed.